2009
DOI: 10.1002/ceat.200900249
|View full text |Cite
|
Sign up to set email alerts
|

New Equipment for Laboratory Studies of Heterogeneously Catalyzed Reactive Distillation

Abstract: In this paper, novel equipment for laboratory studies of heterogeneously catalyzed reactive distillation is described. The so called D+R tray equipment consists of a combination of conventional bubble cap trays with sections that are filled with catalyst and through which the liquid flows when it passes from one distillation tray down to the next. It is designed so that the catalyst can be easily changed, and its amount can be flexibly chosen. In the present study, D+R tray equipment built in glass in the 50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Recently, novel equipment for heterogeneously catalysed reactive distillation, the D+R tray, has been introduced by Schmitt et al (2009). The present work reports results of measurements of the separation capacity of D+R trays.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Recently, novel equipment for heterogeneously catalysed reactive distillation, the D+R tray, has been introduced by Schmitt et al (2009). The present work reports results of measurements of the separation capacity of D+R trays.…”
Section: Introductionmentioning
confidence: 93%
“…It was shown that the catalyst bed in the D+R tray has basically plug-flow characteristics (Schmitt et al, 2009). In the present work, the D+R tray is characterised as a distillation tray by measurements of the separation efficiency.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this context, a new piece of equipment, the so-called D þ R tray, was developed by BASF SE [94]. The D þ R tray consists of a combination of conventional bubble cap trays with sections that are filled with catalyst pellets and through which the liquid flows when it passes from one distillation tray down to the next [95].…”
Section: Figure 88 Column Internals For Reactive Distillation Processesmentioning
confidence: 99%